OKRs - Niven, Paul R. (John Wiley & Sons, Inc., 2023)
Your one-stop guide to implement Objectives and Key Results (OKRs) effectively In business, OKRs--that's short for Objectives and Key Results--are the gold standard for communicating and delivering on what you want to accomplish and how you'll get there. OKRs For Dummies provides you with step-by-step guidance for following in the footsteps of some of the world's leading organizations. Drive focus on what matters most, align and engage teams, and generally maximize the benefits OKRs have to offer, thanks to this easy-to-use guide. You'll learn how to roll out an OKR system that closes the gap between strategy and execution, and helps people at every level organize their daily decisions around shared and important goals. It's time to get strategic with OKRs. Understand the OKR methodology and determine the benefits for your organization Learn how to craft sound OKRs for every level and department of your business Discover best practices and common pitfalls to ensure success when applying OKRs Focus on the three aspects of the OKRs process: Adoption, Engagement, and Alignment Business owners, team leaders, C-suite executives, and coaches will love this friendly how-to manual for joining the OKR movement.